FAKTOR-FAKTOR YANG MEMPENGARUHI PINJAMAN MODAL PETANI IKAN MAS KE PT.BPR DIAN SINARTA DAN PERBANDINGAN PENDAPATAN ANTARA PEMINJAM DAN NON PEMINJAM MODAL - Romyanti, Romyanti; Sriyoto, Sriyoto; Reflis, Reflis (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2004)
A condition which is often find where farmers incapable to providing the capital because weakening of farmer fund which also result in weaken source of farmer's own capital. The effect of this condition, farmers seldom have to use capital from outside both formal and informal sectors. TIhis research was objectived to analyzing factors influencing the amount of goldfish farmer capital loan to PT.BPR DB in Desa Tanjung Harapan Kecamatan Padang Jaya Kabupaten North Bengkulu and compare the level earnings of goldfish farmer among of non capital lender and capital lender farmers to PT.BPR DB. The result showed that amount dependent of family responsibility, goldfish farming income and farmer operating cost last season have influenced on level of the amount of goldfish farmer capital loan, while as such as wide of fishpond, formal education level and farmers age do not have influence on. So, the difference of earnings obtained the average earnings compared to between bigger capital lender to non capital lender.